IL-1β mediates chronic intestinal inflammation by promoting the accumulation of IL-17A secreting innate lymphoid cells and CD4(+) Th17 cells. - Coccia, M; Harrison, O; Schiering, C; Asquith, M; Becher, B; Powrie, F; Maloy, K (2012)
Although very high levels of interleukin (IL)-1β are present in the intestines of patients suffering from inflammatory bowel diseases (IBD), little is known about the contribution of IL-1β to intestinal pathology. Here, we used two complementary models of chronic intestinal inflammation to address the role of IL-1β in driving innate and adaptive pathology in the intestine. We show that IL-1β promotes innate immune pathology in Helicobacter hepaticus-triggered intestinal inflammation by augmenting the recruitment of granulocytes and the accumulation and activation of innate lymphoid cells (ILCs). Using a T cell transfer colitis model, we demonstrate a key role for T cell-specific IL-1 receptor (IL-1R) signals in the accumulation and survival of pathogenic CD4(+) T cells in the colon. Furthermore, we show that IL-1β promotes Th17 responses from CD4(+) T cells and ILCs in the intestine, and we describe synergistic interactions between IL-1β and IL-23 signals that sustain innate and adaptive inflammatory responses in the gut. These data identify multiple mechanisms through which IL-1β promotes intestinal pathology and suggest that targeting IL-1β may represent a useful therapeutic approach in IBD.